Experiences of alcohol use during pregnancy: A qualitative study of pregnant women at risk of acquiring HIV in Cape Town, South Africa - Amanda P. Miller; Lara Court; Sarah Schoetz; Lucia Knight; Kearabetswe Moopelo; Chwayita Ntwasa; Nafisa Wara; Zaynab Essack; Steven Shoptaw; Landon Myer; Dvora Joseph Davey (Elsevier, 2024)
In South Africa, alcohol use during pregnancy is prevalent and associated with increased HIV risk. Developing locally sensitive and contextually appropriate evidence-based interventions to address alcohol use among pregnant and breastfeeding women in South Africa requires comprehensive understanding of the context of perinatal alcohol use and how relationships and lived environments may serve as barriers or supports for alcohol reduction. We conducted twenty in-depth qualitative interviews with isiXhosa speaking women who reported alcohol use during their recent pregnancy and/or recent intimate partner violence in Cape Town, South Africa between September and November 2022. We describe patterns and drivers of ongoing alcohol use during pregnancy and map them onto levels of the socioecological model. Data were analyzed utilizing the interpretivist paradigm and interpretive thematic analysis. Eight women reported alcohol use during pregnancy, sixteen reported experiencing recent IPV, and four women reported both alcohol use during pregnancy and recent IPV. In interviews, commonly cited reasons for continued alcohol use in pregnancy included stress (e.g., due to financial concerns), peer pressure, the central role of alcohol use in socialization and the persistence of misconceptions regarding the safety of alcohol use in pregnancy. Still, despite women reporting social norms that supported continued alcohol use in pregnancy, many altered who they drank with due to fear of judgement from close friends and family, leaving them isolated from their social support system. Interventions aimed at increasing interpersonal support, such as the use of peer mentors, could prove beneficial. Although the clinic provides messaging around the harms of alcohol use in pregnancy, these messages conflict with messaging received from their peers, limiting their impact on behavior. Locally sensitive tailored, relevant programming that intervenes on barriers to reducing alcohol use in pregnancy at multiple levels of the socioeconomic model are vital to effectively addressing this public health issue.